The Importance of Materials Development in Teaching English (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Materials development is an essential aspect of effective English language teaching, encompassing the creation, selection, and adaptation of resources that support learning outcomes. The development of these materials allows teachers to meet students’ linguistic needs, accommodate various learning styles, and engage them in the language-learning process. This article examines the role of materials development, including the types of resources commonly used, the methodologies behind creating and adapting materials, and their impact on student engagement and achievement. By reviewing relevant literature and presenting findings on best practices, this paper underscores the importance of investing in materials development as a key component of English teaching.